Case Report: Recognizing Pneumatosis Intestinalis: A Case of Bowel Ischemia Presenting as Renal Colic - Peter D. Corr (Case Reports in Radiology)
The clinical diagnosis of bowel ischemia is often difficult and the diagnosis can easily be missed unless there is a high index of clinical and radiological suspicion. Bowel ischemia and or infarction must be considered in the differential diagnosis in the older patient with pre-existing coronary artery or generalized vascular disease, cardiac failure, or arrhythmias especially atrial fibrillation and hypertension. An elderly patient with caecal infarction is presented who was initially diagnosed and treated for renal colic.